2018
DOI: 10.1111/pedi.12721
|View full text |Cite
|
Sign up to set email alerts
|

Pet exposure in the family during pregnancy and risk for type 1 diabetes-The prospective ABIS study

Abstract: Exposure to hamster during pregnancy seems to increase the risk of T1D in the child. One possibility could be infection by virus hosted by the pet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Indeed, multiple environmental factors shape the gut microbiome in the first years of life, including geography and household exposures such as pets and siblings (131,138). The ABIS study showed that exposure during pregnancy to cats and dogs conferred no increased risk of T1D, but hamsters did (139).…”
Section: The Gut -Microbiome and Diet The Gut Microbiomementioning
confidence: 99%
“…Indeed, multiple environmental factors shape the gut microbiome in the first years of life, including geography and household exposures such as pets and siblings (131,138). The ABIS study showed that exposure during pregnancy to cats and dogs conferred no increased risk of T1D, but hamsters did (139).…”
Section: The Gut -Microbiome and Diet The Gut Microbiomementioning
confidence: 99%